West Bank and Gaza Environment Priorities Note - World Bank (World Bank, Washington, DC, 2020)
West Bank and Gaza is faced with natural resources scarcity, which constrains livelihoods and development to varying degrees. The inherent scarcity of natural resources is further compounded by increasing degradation of environment and natural resources. Multiple factors contribute to deteriorating conditions of the environment and natural resources. The politically fragile situation continues with impacts of restricted movement on people and goods affecting the environment negatively since there are limited options for expansion of built-up areas and other livelihood opportunities. This has led to unsustainable practices with diminishing quality of the environment and natural resource-based livelihood opportunities for communities. It is therefore vital that the environment and natural resources scarcity be actively managed in a manner that enhances community livelihoods and resilience in order to contribute to sustainable development. The Palestinian authority recognizes the challenges that West Bank and Gaza faces in terms of environment and natural resources and has put in places various strategies and programs to address them. While these sectoral and national strategies and plans are important, they require full implementation and follow-up to ensure better environmental outcomes. This report discusses the key environmental issues faced by West Bank and Gaza, and the way forward to combat the same.